Potential role of aquaculture fish to the recommended nutritional intake (RNI) of children, adults, pregnant and lactating women in Asuogyaman Municipality, Ghana - Emmanuel Kaboja Magna; Ebenezer Koranteng Appiah; Patrick Senam Kofi Fatsi; Emmanuel Delwin Abarike; Kwadwo Ansong Asante; Maxwell Kogbe; Felix Ayarika; Michael Dabi; Joseph Korpone Sakna (Food Chemistry Advances)
This study examined the nutritional composition of farmed fish in Ghana to evaluate their potential contribution to recommended nutrient intakes (RNI) for adults, pregnant and lactating women (PLW), and children. The study used standard methods to analyse the micronutrient and proximate composition of twenty-four samples of three fish species—Heterotitis niloticus, Clarias gariepinus, and Oreochromis niloticus. The protein compositions of Oreochromis niloticus, Clarias gariepinus, and Heterotis niloticus were 17.96 g/100 g, 14.00 g/100 g, and 13.25 g/100 g, respectively. Their lipid values were 0.56 g/100 g, 5.01 g/100 g, and 1.76 g/100 g; ash content was 6.77 g/100 g, 1.90 g/100 g, and 2.94 g/100 g; carbohydrate content was 4.00 g/100 g, 5.02 g/100 g, and 17.20 g/100 g; and moisture content was 70.71 %, 74.07 %, and 64.84 %, respectively. The mineral values ranged from 4.05 to 11.96 mg/100 g (iron), 15.10 to 23.23 mg/100 g (calcium), 1.02 to 8.26 mg/100 g (zinc), 16.52 to 28.42 mg/100 g (potassium), and 10.25 to 19.67 mg/100 g (sodium). The fish species contributed ≥25 % of the zinc and iron RNIs for adults, PLW, and children but were inadequate in providing the recommended daily intake of calcium for the vulnerable groups. Therefore, government interventions are needed to enhance the supply and affordability of farmed fish, to make it more accessible to vulnerable communities.